Does Oil Price Affect the Economic Growth in Somalia Asymmetrically? - Warsame, Abdimalik Ali (International Journal of Energy Economics and Policy, 2022)
Crude oil is one of the most important inputs for production activities, and an increase in its price has a crucial effect on economic growth both in developing and developed countries and Somalia is not an exception. To this end, this undertaking models the asymmetric impact of crude oil price on economic growth in Somalia using the nonlinear Autoregressive Distributed Lag (NARDL) model with annual time series data stretching from 1990 to 2018. The empirical results of the study revealed that oil price asymmetrically affects economic growth in Somalia both in the short and long runs. A positive oil price shock is inconsequential in the long run but impedes economic growth in the short run, while a negative oil price shock has a constructive role in stimulating economic growth in the long run but not in the short run. Nevertheless, the study suggests the implementation of economic diversification towards utilizing other types of energy other than oil and designing policies aimed at increasing energy investments.